2019
DOI: 10.1111/jbi.13545
|View full text |Cite
|
Sign up to set email alerts
|

Human‐mediated dispersal of weed species during the Holocene: A case study of Chenopodium album agg.

Abstract: Aim We hypothesised that during the Holocene, the distributions of species such as crop weeds have been significantly influenced by human activity. We aimed to (a) identify the main centres of diversity of the Chenopodium album agg. species and (b) test if these species colonised Europe from western Asia, most likely due to the westward expansion of agriculture in the Neolithic period. Location Eurasia. Taxon Chenopodium album aggregate (Amaranthaceae). Methods Three cpDNA regions were sequenced in 904 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The human ecological footprint is a good indicator of human influence in that it estimates the quantity of nature necessary to support the consumption habits of one individual, population, product, activity, or service (Sanderson et al, 2002;Wan et al, 2018). Our results provide clear evidence that human influence could drive the expansion of the above-mentioned 5 species on a global scale, although previous studies (e.g., Young and Evans, 1976;Treier and Müller-Schärer, 2011;Alvarado-Serrano et al, 2019;Krak et al, 2019) have shown that weeds could expand in lands degraded by human influence. Such influences of the human ecological footprint include global trade and transportation (Sanderson et al, 2002;Wiedmann and Lenzen, 2018).…”
Section: Contribution Of Human Ecological Footprint Toward Weed Distributionmentioning
confidence: 49%
See 1 more Smart Citation
“…The human ecological footprint is a good indicator of human influence in that it estimates the quantity of nature necessary to support the consumption habits of one individual, population, product, activity, or service (Sanderson et al, 2002;Wan et al, 2018). Our results provide clear evidence that human influence could drive the expansion of the above-mentioned 5 species on a global scale, although previous studies (e.g., Young and Evans, 1976;Treier and Müller-Schärer, 2011;Alvarado-Serrano et al, 2019;Krak et al, 2019) have shown that weeds could expand in lands degraded by human influence. Such influences of the human ecological footprint include global trade and transportation (Sanderson et al, 2002;Wiedmann and Lenzen, 2018).…”
Section: Contribution Of Human Ecological Footprint Toward Weed Distributionmentioning
confidence: 49%
“…Weeds have a high potential to threaten biodiversity and ecosystem functions around the world (Holm, 1969;Tilman et al, 2006;Bajwa et al, 2016;Krak et al, 2019). Owing to their generally broad physiological niches and/or specific traits, weeds can invade human-mediated ecosystems with relative ease (Holm, 1969;Tilman et al, 2006;Shimono and Konuma, 2008;Panetta, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(2012) similarly concluded that colonization of Canada thistle ( Cirsium arvense ) was the result of independent and multiple introductions because of data showing their populations exhibited different genetic fingerprints and lacked a correlation between genetic and geographic distances. C. album populations are most commonly found on disturbed areas ( CABI, 2020 ), and therefore dispersal driven by human activity is likely in these species ( Krak et al., 2019 ). As a result, our lack of correlation between genetic and geographic distances of populations implies that seed dispersal mechanisms and colonization history have influenced the spatial distribution and genetic diversity we observed, similarly to other species ( Heywood et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is autogamous, C. album is highly polymorphic, even compared to other species within the Chenopodium genus. Previous studies explored this taxonomic complexity through cytology ( Mukherjee, 1986 ), karyotypic analysis ( Kolano et al., 2008 ), flavonoid profiling ( Rahiminejad and Gornall, 2004 ) random amplified polymorphic DNA profiles ( Rana et al., 2010 ), ISSR marker analysis ( Rana et al., 2012 ) and cpDNA regions sequencing ( Mandák et al., 2018 ; Krak et al., 2019 ). A. retroflexus is partly autogamous and a study of the genetic composition of Central European A. retroflexus using isoenzyme analysis showed moderate levels of genetic diversity and strong evidence for inbreeding within populations compared to other herbaceous plants ( Mandák et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on archaeological and genetic studies, human‐mediated movement of farm animals and domesticated plants during the Neolithic era in western or eastern Eurasia has been well documented (e.g. Krak et al, 2019; Li, Tian, et al, 2019; Ottoni et al, 2013). More recent studies have further proven that human dispersal and Eurasia‐wide trade play an essential role in contemporary species distributions (Feuerborn et al, 2021; Kawakubo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%